The effects of a carbohydrate hydrogel system for the delivery of bicarbonate mini-tablets on acid-base buffering and gastrointestinal symptoms in resting well-trained male cyclists - Gough, L. A.; Sparks, S. A. (Sports Medicine - Open, 2024)
Background A new commercially available sodium bicarbonate (SB) supplement claims to limit gastrointestinal (GI) discomfort and increase extracellular buffering capacity. To date, no available data exists to substantiate such claims. Therefore, the aim of this study was to measure blood acid-base balance and GI discomfort responses following the ingestion of SB using the novel "Bicarb System" (M-SB). Twelve well-trained male cyclists completed this randomised crossover designed study. Maximal oxygen consumption was determined in visit one, whilst during visits two and three participants ingested 0.3 g·kg-1 BM SB using M-SB (Maurten, Sweden) or vegetarian capsules (C-SB) in a randomised order. Finger prick capillary blood samples were measured every 30 min for pH, bicarbonate (HCO3-), and electrolytes (potassium, chloride, calcium, and sodium), for 300 min. Visual analogue scales (VAS) were used to assess GI symptoms using the same time intervals.